THE PARLIAMENTS OF CANADA AND PAKISTAN: A COMPARATIVE ANALYSIS OF STRENGTHS AND WEAK - Akram, Sidra; Azhar, Mian Muhammad; Akhtar, Shakil; Mubarak, Husni; Haq, Muhmmad Ikram Ul (Humanities & Social Sciences Reviews, 2021)
Purpose: The main purpose of this study is to make a deeper analysis of the parliament of Canada and Pakistan. This research deals with comparing two similar parliamentary systems. The two countries, i.e. Canada and Pakistan were chosen because of their majority electoral system and to a lesser extent, alike political trends. This research analyzed the weaknesses and strengths of both the legislative systems. Method: Data related to this topic has been collected from secondary sources such as reports, journal articles, and books. This research work is analytical as well as descriptive in nature. Qualitative techniques have been applied to investigate the research questions. Main Findings: This study acknowledges that the parliamentary form of government is the most representative and most efficient system of government that is running successfully in different countries. Parliament safeguards the political views of the citizens and thus provides them with all possible opportunities for more participation in the government. It creates a cohesive and strong party system. The main finding to be acquired from this study is that one problem that is common to both nations is provincial imbalance. However, overall it can be said that Canada has accommodated its provinces effectively through its responsible government, democratic system, and granting maximum autonomy. Another factor that is a major problem in Pakistan but not so in Canada is the branches of government overstepping their jurisdiction. Application of the Study: Using the yardstick of the function of legislation and making comparative references with other political systems was very useful in summarizing this research. Whatever weaknesses and criticisms may be discussed the overall fact is that the job done by these parliaments is undoubtedly necessary and useful and it is hoped this study may serve as a guideline for future parliaments to make them more efficient. The Originality of the Study: This research argues that a parliamentary system is a more desirable and efficient system of government than others. This research explains the differences between both these systems. Both the houses of these parliaments provide separate services that require separate investigation and throw further light on the subject.